Large fiscal episodes and sustainable development some international evidence - Joshua Aizenman; Yothin Jinjarak; Hien Nguyen; Donghyun Park (Asian Development Bank (ADB), 2021)
This paper examines the association between episodes of large fiscal impulses (expansions and adjustments) and sustainable development indicators (prosperity, resilience, and inclusivity). We provide country studies of Chile, Poland, South Africa, and Thailand, examining the components of government expenses and tax revenues, and reporting four stylized patterns from the analysis as follows: (i) Fiscal expansions led to higher growth rates and reduced negative trade-offs, e.g., pollution and poor-health mortalities associated with economic growth. (ii) Fiscal adjustments led to a more inclusive economy, lowered poverty headcounts, improved sanitation, and increased cleaner technology access. (iii) Fiscal expansions followed an increase in direct taxes (especially corporate taxes) and a decline in social contributions, and preceded a decline in other direct taxes and an increase in wage bills. (iv) Fiscal adjustments followed a decline in other direct taxes and social contributions, an increase in wage bills, and preceded a decline in government consumption expenditure and transfers. In light of these findings, domestic resource mobilization should consider the time paths of the taxes and expenditure components to understand their empirical linkages with sustainable development outcomes in the respective countries.
Keywords: E62; H11; O11; 330; sustainable development; tax base; government expenses; large fiscal changes